2017
DOI: 10.1002/lary.26494
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspirated barium sulfate, iodixanol, and diatrizoic acid on survival and lung injury in a lagomorph model

Abstract: NA Laryngoscope, 127:E148-E152, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Aspiration of saline, ICA, and NICA did not cause any pathological pulmonary changes and immunological responses in the chronic phase. The high‐osmolality of ICA has been associated with pulmonary congestion in the acute stage, and pulmonary congestion and edema after ICA aspiration are improved within a few days after aspiration . In the chronic stage, it is reported that the reactions to ICA aspiration considerably decreased by the 42nd day, and a similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Aspiration of saline, ICA, and NICA did not cause any pathological pulmonary changes and immunological responses in the chronic phase. The high‐osmolality of ICA has been associated with pulmonary congestion in the acute stage, and pulmonary congestion and edema after ICA aspiration are improved within a few days after aspiration . In the chronic stage, it is reported that the reactions to ICA aspiration considerably decreased by the 42nd day, and a similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The use of swallowing function tests for evaluating patients with dysphagia is prevalent . Contrast videofluoroscopic swallow studies (VFSSs) are an essential part of the diagnostic checkup for persons with a suspected swallowing disorder . Radiographic contrast agents (CAs) are essential in VFSS and upper gastrointestinal studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic contrast videofluoroscopic swallow studies (VFSSs) are an essential part of the diagnostic workup of persons with dysphagia . Radiographic contrast agents (CAs) are also essential in esophagography and more distal upper‐gastrointestinal studies . Barium (Ba) sulfate, nonionic contrast agents (NICAs: iohexol, iodixanol), and ionic contrast agents (ICAs: diatrizoic acid) are the most common CAs currently used for VFSS and upper‐gastrointestinal investigations.…”
Section: Introductionmentioning
confidence: 99%
“…32-37 Second, in cases where contrast evaluation is necessary, some other lung-friendly contrast agents like iopydol, hytrast, and iodixanol can be considered. 12,19,38,39 Last, proper posturing and maneuvers, for example, rotating the head while lying on the side and chin touching the neck during barium swallow, can prevent aspiration of barium sulfate. 40 …”
Section: Discussionmentioning
confidence: 99%